Highly selective CuO/γ–Al2O3 catalyst promoted with hematite for efficient methanol dehydration to dimethyl ether. (29th March 2018) - Armenta, M.A.; Valdez, R.; Quintana, J.M.; Silva-Rodrigo, R.; Cota, L.; Olivas, A.
Abstract: A recent alternative for replacing traditional hydrocarbons like gasoline, diesel, and natural gas, is the use of dimethyl ether (DME), which is more environmentally friendly. One of the ongoing challenges is to catalyze methanol dehydration for selectively producing the DME (2CH3 OH → CH3 OCH3 + H2 O). It is established that the CuO catalyst over alumina performs the methanol dehydration, but the formation of by-products is the main drawback. For these reasons, we synthesized a CuO/γ–Al2 O3 catalyst promoted with hematite aiming to enhance the activity toward DME at atmospheric conditions. The resulting bimetallic catalyst (CuO-Fe2 O3 /Al2 O3 ) performed a 70% conversion at 290 °C, which is similar to other catalysts recently reported in the literature but done in harsh conditions. In addition, this bimetallic catalyst exhibited a 100% in selectivity toward the DME production. XPS spectra of the fresh and used catalyst suggested that the chemical oxidation states of Cu and Fe remain without change. After regenerating the catalyst at 600 °C for 2 h in air, it performed at a similar catalytic conversion, confirming the reusability of the as-synthesized material and reducing the environmental impact. Graphical abstract: Highlights: DME produced from methanol dehydration reaction using CuO catalyst promoted by Fe2 O3. CuO-Fe2 O3 /γ–Al2 O3 reached selectivity to DME of 100% at any reaction temperature. Oxides oxidation state was preserved after the reaction, showing stability. Bimetallic presents the greatest number of acidic sites, which favor the reaction.